MUSLIM COMMUNITY OPINION ON THE FREE NUTRITIOUS MEAL PROGRAM AS A SOCIAL WELFARE POLICY: A STUDY IN SEI SENTOSA VILLAGE, LABUHANBATU REGENCY - Selasih, Dian; Khatibah, Khatibah; Parmanda, Wahyu Rizky (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study examines public opinion within a Muslim community regarding the Free Nutritious Meal Program (Program Makan Bergizi Gratis/MBG) as a government social welfare policy in Sei Sentosa Village, Panai Hulu District, Labuhanbatu Regency. Situated within the framework of Islamic community development and social welfare, the study explores community experiences, perceptions, and responses toward the program's implementation. A qualitative method with a phenomenological approach was employed. Data were collected through in-depth interviews with seven informants comprising a program coordinator, a village secretary, a teacher, two parents, and two students as program beneficiaries, complemented by field observation and documentation. The findings indicate that community opinion toward the MBG Program is generally positive. The program is perceived as effective in fulfilling students' nutritional needs, improving learning concentration and motivation, and providing economic relief for families by reducing household expenditure. The program also contributes to improving community welfare, particularly in health and education — two dimensions closely aligned with Islamic values of human dignity (karamah) and collective well-being (maslahah). However, implementation challenges remain, including delays in food distribution, limited menu variation, and inconsistent food quality. Public opinion manifests not only as support but also as constructive social critique reflecting the community's role as active participants in policy governance. This study concludes that the success of the MBG Program is strongly influenced by implementation effectiveness, service quality, and program socialization, and recommends continuous evaluation to optimize its social welfare outcomes.